Comparative study on toxoplasma infection between Malaysian and Myanmar pregnant women - Andiappan, H.; Nissapatorn, V.; Sawangjaroen, N.; Nyunt, M.H.; Lau, Y.L.; Khaing, S.L.; Aye, K.M.; Mon, N.C.N.; Tan, T.C.; Kumar, T.; Onichandran, S.; Adenan, N.A.M. (BMC, 2014)
Background: Toxoplasma gondii, an obligate intracellular protozoan parasite, causes a disease called toxoplasmosis which can sometimes be acquired congenitally by a newborn from an infected mother. This study aimed to determine the seroprevalence of Toxoplasma infection and its associated risks among 219 and 215 pregnant women from Malaysia and Myanmar, respectively. Methods: Anti-Toxoplasma IgG and IgM antibodies were screened by using standard commercial ELISA kits. The socio-demographic, obstetrics and risk factors associated with Toxoplasma infection data were compared between the two countries. Results: The overall prevalence of Toxoplasma infection in Malaysian pregnant women (42.47%; 95% CI = 36.11-49.09) was significantly higher (p < 0.05) than Myanmar pregnant women (30.70%; 95% CI = 27.92-37.16). By univariate analysis, this study identified that age group, education, parity, awareness on toxoplasmosis and consumption of undercooked meat were significantly associated (p < 0.05) with Toxoplasma seropositive Malaysian pregnant women but none of these factors associated with Toxoplasma seropositive Myanmar pregnant women. In comparison using univariate analysis between the two countries, it was found that Toxoplasma seropositive Malaysian pregnant women was associated with aged 30 years and above, secondary or lower-secondary level of education, the third trimester of pregnancy, having one child or more, lacking awareness of toxoplasmosis, absence of bad obstetrics history, having no history of close contact with cats or soil, living on a farm and also consumption of undercooked meat, unpasterized milk or untreated water. Avidity measurement was used to confirm the stages of Toxoplasma infection in pregnant women who were positive for both IgG and IgM antibodies and found all were infected in the past. Conclusion: From our study, Toxoplasma screening and its risk measurement in pregnant women is firmly recommended for monitoring purposes and assisting proper management, including diagnosis and treatment during antenatal period. Also, it is necessary to initiate preventive measures for Toxoplasma infection among reproductive-age women in general and seronegative pregnant women in particular. Avidity measurement should be incorporated in Toxoplasma routine screening, especially with the availability of a single serum sample to assist in the diagnosis.